Cellular correlates of gray matter volume changes in magnetic resonance morphometry identified by two-photon microscopy - Asan, Livia; Falfán‐Melgoza, Claudia; Beretta, Carlo Antonio; Sack, Markus; Zheng, Lei; Weber-Fahr, Wolfgang; Kuner, Thomas; Knabbe, Johannes (Scientific reports, 2021)
Magnetic resonance imaging (MRI) of the brain combined with voxel-based morphometry (VBM) revealed changes in gray matter volume (GMV) in various disorders. However, the cellular basis of GMV changes has remained largely unclear. We correlated changes in GMV with cellular metrics by imaging mice with MRI and two-photon in vivo microscopy at three time points within 12 weeks, taking advantage of age-dependent changes in brain structure. Imaging fluorescent cell nuclei allowed inferences on (i) physical tissue volume as determined from reference spaces outlined by nuclei, (ii) cell density, (iii) the extent of cell clustering, and (iv) the volume of cell nuclei. Our data indicate that physical tissue volume alterations only account for 13.0% of the variance in GMV change. However, when including comprehensive measurements of nucleus volume and cell density, 35.6% of the GMV variance could be explained, highlighting the influence of distinct cellular mechanisms on VBM results.
Gesehen am 22.02.2021